Attributing Weight to Virtual Objects in Preschoolers - S.G. Krylova; Y.E. Vodyakha (Moscow State University of Psychology and Education, 2022)
Modern education is undergoing a process of digital transformation at all levels, including preschool. The psychologically founded use of digital technologies makes it relevant to study the child's ideas about the objects of the digital environment (virtual objects). This empirical study is aimed to test two hypotheses: 1) Preschoolers attribute the quality of weight to virtual objects; 2) Preschoolers perceive virtual objects as light-weighted. 53 children, 3.5 to 5 years old, participated in this study (M=4.3; SD=0.41). The study includes experimental technique (H. Kloos, E.L. Amazeen), assessed children's perception of weight based on their interaction with these objects without verbal self-report. The weight was operationalized through the location on a hill model (slope length - 40 cm) of two real objects (lightweight - 27 g, heavy - 170 g) and a virtual object, which was previously "lifted on the shelf" on a tablet PC screen. 92.5% of participants designated a specific place on the hill for the virtual object, suggesting they attributed weight to it. For 70.4% of children, the placement of a virtual object (Ме=40 см) does not significantly differ (Temp=13.5 р=0.933) from the placement of a light real object (Ме=40см). For 18.2% of children, the placement of a virtual object (Ме=14.5см) does not significantly differ (Temp=11.5 р=0.673) from the placement of a heavy real object (Ме=12.25см). Further research is necessary to better understand factors contributing to preschoolers' perception of virtual objects wight.